Pengaruh Lingkungan Kelas Menggunakan My Class Inventory-Short Form terhadap Hasil Belajar - Az-Zahra, Shakira; Fadillah, Nur; Suryani, Elma; Lisdiana, Hayyun (Jambura Journal of Educational Chemistry, 2024)
This research aims to determine the influence of the classroom environment using the My Class Inventory-Short Form instrument on learning outcomes. The research method used is a quantitative method with survey techniques using the My Class Inventory-Short Form (MCI-SF) instrument which consists of 5 dimensions, namely satisfaction, friction, competitiveness, difficulty and cohesiveness with a total of 25 statements. Based on the research results, the highest average was in the satisfaction dimension at 4.09 and the lowest was in the friction dimension at 1,50. This shows that in the satisfaction dimension, the average student agrees with a pleasant classroom environment. Meanwhile, in the friction dimension, the average student stated that they strongly disagreed that pupils are always fighting with each other. Based on the research carried out, the value of tcount = 13,267, so the value of tcount > ttable. This means that there is an influence between the classroom environment on the learning outcomes of class XI students at SMAN 70 Jakarta with a percentage of the influence of the learning environment of 85,4% which is included in the strong category.